Weight changes and reproduction in female Blue-billed and Musk Ducks, compared with North American Ruddy Ducks - Briggs, S V (Wildfowl, 1988)
Female Blue-billed and Musk Ducks both increase in body weight prior to breeding. Blue-billed Ducks increase by 369 g (46%) and Musk Ducks by 327 g (24%) between pre-breeding and breeding. These weight gains, especially in Blue-billed Ducks, are high compared with those in related North American Ruddy Ducks. It is suggested that this difference is because North American Ruddy Ducks have to migrate long distances to breed whereas Blue-billed and Musk Ducks do not.